(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2022)
The study aimed to examine the psychometric properties of the Urdu version of Patient Satisfaction with Pharmacist Services Questionnaire (PSPSQ 2.0). We applied the forward-backward procedure to translate the PSPSQ 2.0 in the Urdu language. The test-retest reliability was assessed through Cronbach’s alpha reliability analysis. The validity of the translated PSPSQ 2.0 was constructed by using Confirmatory Factor Analysis (CFA) through principal axis factoring extraction and Oblique rotation with Kaiser Normalization onto 2 predetermined factors. The Quality of Care (QOC) construct exhibited Cronbach’s alpha values of 0.900 (Test) and α = 0.871 (Retest) at two-time points. The Interpersonal Relationship (IPR) Construct had alpha values of 0.845 (Test) and α = 0.819 (Retest). The Kaiser-Meyer-Olkin measure of sampling adequacy for the factor analysis was 0.899. Barlett’s Test of Sphericity was significant (Chi-square = 1192.72; p < 0.05) revealing relationships of the data and suitability of CFA. Two factors explaining the total variance of 40% were extracted whereby loading values were acceptable (> 0.50) for all items of the translated version of PSPSQ 2.0. Results of this study conclude that the translated version of PSPSQ 2.0 is a valid instrument in regions where Urdu is a prime language of communication.